A case report of oculopharyngodistal myopathy with 126 CGG repeat expansions in RILPL1 - Wang, Wenjing; Yin, Tielun; Zhang, Xinyu; Wang, Zhaoxia; Wang, Tianyun; Zhang, Shuo; Zhang, Yingshuang; Fan, Dongsheng (Frontiers in Genetics, 2025)
BackgroundOculopharyngodistal myopathy (OPDM) is a rare hereditary muscle disease characterized by progressive ptosis, ophthalmoplegia, dysphagia, dysarthria, and distal muscle weakness. The genetic basis was identified in 2019 with CGG repeat expansions in the noncoding region of LRP12. Similar expansions in GIPC1, NOTCH2NLC, and RILPL1 were later linked to OPDM, classifying the disease into OPDM1-4. OPDM4, associated with RILPL1, was discovered in 2022 with a few confirmed cases worldwide, leaving its clinical features and pathogenic mechanisms largely unexplored.Case presentationWe present a patient with OPDM4 who had suffered progressive ptosis, external ophthalmoplegia, pharyngeal weakness, facial muscle weakness, and distal limb weakness over the past 20 years. Electromyography (EMG) revealed myogenic damage and normal H-reflex latency. A biopsy of the left biceps brachii revealed myogenic changes with atypical rimmed vacuoles in some muscle fibers. Screening for extra-muscular system involvement revealed no obvious involvement of the heart or central nervous system. Genetic analysis confirmed 126 CGG repeat expansions in RILPL1 and excluded abnormal CGG repeat expansions in LRP12, GIPC1, and NOTCH2NLC.ConclusionThis case broadens the spectrum of CGG repeat numbers in the RILPL1 gene associated with OPDM4. In addition, systematic medical examinations revealed several new characteristics of OPDM4, which have not been reported previously, such as normal H reflex, potential mild cognitive impairment, etc. These findings expand our knowledge of the phenotypic spectrum of diseases caused by repeat CGG expansions in RILPL1.